On the obligation to be rational - Shackel, Nicholas (2004)
I formulate what I believe to be a correct account of the normativity of rationality. I identify two opposing doctrines which I call instrumentalism and rationalism. Instrumentalism says there are no obligations to be rational intrinsic to rationality, but that being rational is instrumental to doing what ought to be done. Rationalism says there are intrinsically rational obligations. I give arguments for instrumentalism and show how a bifurcation in normativity undermines characteristic Aristotelian and Kantian arguments in support of rationalism. I concede that the confrontation between instrumentalism and rationalism cannot be settled in the thesis, since it depends in part on a fundamental dispute about the nature of rationality. However, the doctrine of instrumentalism gives a particularly clear picture of how obligation and rationality are related, and I believe I have shown instrumentalism to be a doctrine which must be taken seriously. Consequently, I believe my thesis to be a contribution to the Humean view of the relation of obligation and reason.